Relationship of instagram content, instagram influencer, and perceived value of the product towards customer purchase intentions of photography service industry - Siregar, Bian Hidema Zuhrilian; Mirzanti, Isti Raafadini (Journal of Innovation, Business and Entrepreneurship, 2019)
The trend of buying and selling of photography service is increasing. Furthermore, with the support of technology’s rapid growth, the use of social media is helping the business to grow. For instance, on Instagram, there are lots of users that sell their photography services and look for it. This phenomenon can be proved by the high number of photography services tag photos on Instagram, which acts as the media for customers to see the product, access information, and assess the product. The main objective of this study is to analyze the relationship of Instagram content, Instagram influencer, and perceived value of the product towards customer purchase intention. This research can be implemented to attract the purchase intention of photography services on Instagram. After reading previous studies, the researcher continues to analyze the relationship by using quantitative method through questionnaires. The questionnaires will be distributed to the customers who will use photography service or people who have been used photography service on Instagram and live in Jakarta/Bandung. In this research, the independent variables are Instagram content, Instagram influencer, and perceived value of the product. While the dependent variable is purchase intention. The multiple regression analysis is used to analyze the relationship between the independent variables with the dependent variable. After all the test is completed, the researcher will make conclusion based on the data analysis to answer the research question. Recommendations will also be given and is expected to solve the problem which exist in this research. Lastly, the researcher will also give some insights related to the further research.Keywords: Photography Service Industry, Instagram content, Instagram Influencer, Perceived value of the Product, Purchase Intention